2022
DOI: 10.1128/cmr.00094-21
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Respiratory Viral and Fungal Coinfections

Abstract: Individuals suffering from severe viral respiratory tract infections have recently emerged as “at risk” groups for developing invasive fungal infections. Influenza virus is one of the most common causes of acute lower respiratory tract infections worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 575 publications
(597 reference statements)
0
80
0
1
Order By: Relevance
“…It has been suggested that COVID-19-associated pulmonary aspergillosis (CAPA) is a contributing factor to mortality in patients with severe COVID-19 (Salazar et al, 2021). In our series, 7.69% of the patients showed CAPA.…”
Section: Discussionmentioning
confidence: 56%
“…It has been suggested that COVID-19-associated pulmonary aspergillosis (CAPA) is a contributing factor to mortality in patients with severe COVID-19 (Salazar et al, 2021). In our series, 7.69% of the patients showed CAPA.…”
Section: Discussionmentioning
confidence: 56%
“…The significant lower number of alveolar macrophages in non-treated mice could point to a potential immune dysregulation through which influenza predisposes to a fungal superinfection. It is known that type I IFN induced by influenza can inhibit the production of the chemokine CCL2, which is important for macrophage recruitment [31,32]. Besides an effect on recruitment, influenza virus infection can result in depletion of alveolar macrophages and can impair the macrophage phago-cytic activity important for fungal clearance [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that type I IFN induced by influenza can inhibit the production of the chemokine CCL2, which is important for macrophage recruitment [31,32]. Besides an effect on recruitment, influenza virus infection can result in depletion of alveolar macrophages and can impair the macrophage phago-cytic activity important for fungal clearance [31][32][33]. However, further comprehensive immunological studies are needed to identify the immunological mechanism behind IAPA.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the incidence of CAPA varies considerably among countries and units and is likely underdiagnosed, further contributing to the poor outcomes observed [ 9 , 10 , 11 , 12 ]. While this is a new entity, it is important to recognise a similar presentation is well described in post influenza patients [ 13 ]. Both of these entities are associated with increased mortality, morbidity, duration of hospital stay and mechanical ventilation duration [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%